Hydrogen Sulfide Promotes Cardiomyocyte Proliferation and Heart Regeneration via ROS Scavenging. (22nd May 2020) - Pei, Jianqiu; Wang, Fang; Pei, Shengqiang; Bai, Ruifeng; Cong, Xiangfeng; Nie, Yu; Chen, Xi
Abstract : Neonatal mouse hearts can regenerate completely in 21 days after cardiac injury, providing an ideal model to exploring heart regenerative therapeutic targets. The oxidative damage by Reactive Oxygen Species (ROS) is one of the critical reasons for the cell cycle arrest of cardiomyocytes (CMs), which cause mouse hearts losing the capacity to regenerate in 7 days or shorter after birth. As an antioxidant, hydrogen sulfide (H2 S) plays a protective role in a variety of diseases by scavenging ROS produced during the pathological processes. In this study, we found that blocking H2 S synthesis by PAG (H2 S synthase inhibitor) suspended heart regeneration and CM proliferation with ROS deposition increase after cardiac injury (myocardial infarction or apex resection) in 2-day-old mice. NaHS (a H2 S donor) administration improved heart regeneration with CM proliferation and ROS elimination after myocardial infarction in 7-day-old mice. NaHS protected primary neonatal mouse CMs from H2 O2 -induced apoptosis and promoted CM proliferation via SOD2-dependent ROS scavenging. The oxidative DNA damage in CMs was reduced with the elimination of ROS by H2 S. Our results demonstrated for the first time that H2 S promotes heart regeneration and identified NaHS as a potent modulator for cardiac repair.